The precariousness of knowledge workers: hybridisation, self-employment and subjectification. (1st December 2016) - Annalisa Murgia; Lara Maestripieri; Emiliana Armano
Abstract : In knowledge-based industries, work is circumscribed by the cognitive frames of creativity in the representations of subjects, but simultaneously demands adaptability, in a context in which deregulation and individualisation are now normal. The ethics of self-activation are therefore inextricably intertwined with the demands of intensification, standardisation and self-commodification. The first volume of this Special Issue – which is made up of two different parts – focuses on the phenomena of hybridisation, self-employment and subjectification, at the core of the experiences of precarious workers in knowledge societies. This article introduces the first part of the two-part Special Issue on the precariousness of knowledge workers.